Comparison of trace element concentrations in cancerous and noncancerous human endometrial and ovary tissues. Issue 1 (1st January 2007) - Yaman, M.; Kaya, G.; Simsek, M.
Abstract : Question of whether trace metal concentrations in tissues are increased or decreased in cancerous patients in comparison with noncancerous patients has not been answered yet, due to the fact that the data known in this field are rare and have contradictory results. Although Zn and Cu concentrations in serum and tissues of cancerous patients have extensively been studied, the precise role of these metals in carcinogenesis is not clearly understood. There are few studies on the concentrations of essential and toxic trace/minor metals in human tissue samples in comparison with serum and plasma samples. Trace metal concentrations including Cd, Cu, Zn, Fe, Mg, Ca, and Ni in both cancerous and noncancerous endometrial, ovary, and cervix uteri tissues were determined by atomic absorption spectrometry. The tissue samples were digested by using microwave energy. Slotted tube atom trap was used to improve the sensitivity of copper and cadmium in flame atomic absorption spectrometry determination. The concentrations of iron in cancerous endometrial tissues were found to be significantly higher than those in noncancerous samples ( P < 0.01). On the contrary Fe, Zn concentration in cancerous endometrial tissue was found to be lower significantly than those in noncancerous samples ( P = 0.005), whereas the other studied metals were not observed different. Furthermore, Cu and Ca concentrations in cancerous ovary samples were observed to be higher than those in noncancerous ovary tissues ( P < 0.01 for Cu and P = 0.1 for Ca), whereas Mg, Fe, and Zn levels in cancerous ovary samples were not found to be different than those in noncancerous tissues.